COUNSELLING MEDIA AND SUICIDAL IDEATION AMONG UNDERGRADUATES IN A NIGERIAN UNIVERSITY - Olusegun F. Adebowale; Mayowa Alexius Gbore (Universitas Pendidikan Indonesia, 2023)
The study investigated the prevalence of suicidal ideation among the undergraduates of a Nigerian university. It determined the individual and relative effectiveness of face-to-face, online and blended media of counselling on suicidal ideation, and the moderating influences of self-concept and peer relationship. The study adopted a pre-test, post-test experimental control group design and a sample of 1200 undergraduates selected by multi stage sampling. Data were collected using the “Adult Suicidal Ideation Questionnaire” developed by Reynolds (1991) and were analyzed using Kruskal Wallis H-test, Wilcoxon ranked test, ANCOVA and Two-way ANOVA. The results showed that although, all the three counselling media were found to be effective on suicidal ideation, the blended media was found to be the most effective (F= 7.511, p 0.05). Self-concept had a significant moderating influence on the three counselling media (F= 8.952, p 0.05) while peer relationship did not (F= 3.152, p 0.05).